Effects of reading strategies on grade one children’s phonemic awareness performance - Solomon Melesse; Chanyalew Enyew (Intelektual Pustaka Media Utama, 2020)
This study examined the effects of language teaching strategies in Amhara region, Ethiopia on children’s phonemic awareness reading performance. To this end, one hundred and two grade one children of two intact sections (n=50) and (n=52) were selected and participated as experimental and control groups, respectively. The research employed quasi-experimental pre- and post-test research design that aimed at examining the effects of reading strategies in children’s phonemic awareness performance. Besides, the researchers collected data through non-participant observation and teacher self-reflection reports. To analyze children’s phonemic awareness, paired samples t-test was computed using pre- and post-test scores of the children. To analyze the qualitative data, researchers employed narratives based on categories formed considering the basic themes of the research questions of this paper. Findings indicated that phonemic awareness reading strategies used in Amhara region could improve children’s phonemic awareness performance. Furthermore, observation and teachers’ reflections showed that there were positive results on the application of the strategies in improving children’s phonemic awareness. Eventually, recommendations and implications for further research were suggested.